The Problem Of Great Precision Juridical And Sociological In Corruption Case - Sidik Sunaryo; Shinta Ayu Purnamawati; Haris Thofly (LPPM of NAROTAMA UNIVERSITY, 2018)
The problem of juridical the award judge number: 56 / Pid / 2010 / PT.SBY, has not followed the legal formal in KUHAP as article; 183, 184, 185,186, 187, 191, 192, 194, 195, 196, 197, 199, 200, 202. The award the judge also could not prove a whole elements of a mistake. Judge only prove a small portion of element of the mistakes made by the defendant. The problem of sociological the award judge number: 56 / Pid / 2010 / PT.SBY, not capable of being description assurance of fairness and expediency. The award judge only description a form of unprofessional judge cutting off. The award judge only prove mistrust construction think of judge in understanding the iniquity of the defendant, therefore the award the judge was not salutary.